Exponential Model of Token Bucket System - Juraj Smiesko (Communications - Scientific letters of the University of Zilina, 2003)
In the presented paper we use the Theory of Markovov Chains for simulation of a simple model of the Token Bucket System (TBS). In the first section we deal with a steady-state analysis of the TBS with Exponential model of On-Off Source of human speech. We develop recurrent formulas for state probabilities of the TBS. In the second section we use real parameters of VoIP and we calculate characteristic of the TBS. In the last section the values of probability of a loosing packet are approximated by more types of regression functions. It is shown that the cubic approximation is the most efficient. Using this function we can directly compute values of probability of a loosing packet.